Progress and Perspectives of Geotechnical Anchor Bolts on Slope Engineering in China - Du, Yan; Li, Heng; Chicas, Santos D.; Huo, Leichen (Frontiers in Environmental Science, 2022)
Geotechnical anchoring technology is an important tool for disaster prevention and mitigation in slope engineering. Anchor bolts which are commonly used in slope engineering can be divided into prestressed anchors and non-prestressed anchors. Due to the superiority of anchor support technology, research on various aspects of anchor bolts, such as mechanical mechanism, anchorage effect and the development of new-type anchor bolts, haves been significant research topics for scholars. This mini-review sums up the diverse past and current literature of anchor support technology of slope engineering in China. It focuses on the characteristics, applications, research methods and practical cases of anchor bolts, and briefly describes the history of slope anchor bolts development in China in the past three decades. Nowadays, the demand of engineering construction processes is increasing, and the engineering geological conditions are becoming more complex, which promotes the development of anchor support technology. At the international level, achieving carbon neutrality is both an international trend and a general objective. Against the background of global commitment to carbon neutrality, the potential future perspectives for the developments of anchor support technology have been prospected in the light of actual engineering needs.